ECONOMETRIC ANALYSIS OF TOURISM CLUSTER IMPACT ON REGIONAL ECONOMIC GROWTH: EVIDENCE FROM JIZZAKH REGION - Kamolov , Dostonbek (Scientific practical conference, 2026)
This study examines the impact of tourism cluster development on regional economic growth in Jizzakh region using econometric analysis. In the context of the digital economy, tourism clusters are considered as key drivers of regional development, contributing to employment, infrastructure development, and income generation. The research aims to analyze the relationship between tourism cluster indicators and regional economic performance through a regression model. The methodology includes statistical analysis, econometric modeling, and comparative evaluation of key variables such as tourist arrivals, investment in tourism infrastructure, and regional gross product. The results reveal a strong positive correlation between tourism cluster development and economic growth. In particular, investment and infrastructure variables show significant influence on regional output. The findings suggest that strengthening tourism clusters can enhance regional competitiveness and contribute to sustainable economic development. Policy implications include improving infrastructure, increasing investment, and integrating digital technologies into tourism management.